Social Media Influence on Consumption of Personal Care Products: Implications for Sustainable Consumption - Sankaridevi, B; Karthikram, M (Shanlax International Journal of Management, 2025)
There are around 5.07 billion active social media users of different social media platforms. Apart from traditional marketing, it allows the brands to engage with their prospective customers in a very interactive way that results in customer engagement. Generally, the advancement of social media has changed customer behavior, buying patterns, purchase decisions of the customers. Brands also use influencers with a reasonable follower base as a part of their promotion strategy. However, this research undergoes on how social media (such as new age social media like Instagram, YouTube short videos) creates an impact in the buying decisions of the customers and the implications of Sustainable consumption. This research explores how social media influence customers about consumption of personal care products and also about inferences of Sustainable consumption. This study collects the data through a questionnaire-based survey among all social media users. The sample size for data collection is 393 samples. The results will give a better insight into the consumption of customers and help to give suggestions for implications of Sustainable consumption of personal care products. Ultimately, this research relies on the impact of social media influence in the purchase intention of the customers. In addition to that, it analyzes the purchase intention of the customers due to social media usage and the implications of Sustainable consumption only based on their needs.